2023
DOI: 10.3389/fmolb.2023.1118377
|View full text |Cite
|
Sign up to set email alerts
|

A novel myeloid cell marker genes related signature can indicate immune infiltration and predict prognosis of hepatocellular carcinoma: Integrated analysis of bulk and single-cell RNA sequencing

Abstract: Myeloid cells are physiologically related to innate immunity and inflammation. Tumor-associated myeloid cells gained increasing interest because of their critical roles in tumor progression and anticancer immune responses in human malignancies. However, the associations between tumor-associated myeloid cell-related genes and hepatocellular carcinoma have yet to be revealed. Here, through the integrating analysis of bulk and single-cell RNA (scRNA) sequencing of public HCC samples, we developed a gene signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In addition, immune correlation analysis revealed that SPP1 expression was higher in resting CD4 memory T cells and lower in regulatory T cells in the diagnosis of biliary atresia, suggesting that SPP1 mediated CD4+ T-cell and regulatory T-cell infiltration ( 29 ) ( Figure 1A ). Additionally, integrated analysis of bulk and single-cell RNA sequencing data showed that SPP1 was positively associated with myeloid cell infiltration but negatively associated with CD4/CD8 cell infiltration in the prognosis of patients with hepatocellular carcinoma ( 30 ) ( Figure 1A ).…”
Section: Spp1 Signaling and Immune Cellsmentioning
confidence: 99%
“…In addition, immune correlation analysis revealed that SPP1 expression was higher in resting CD4 memory T cells and lower in regulatory T cells in the diagnosis of biliary atresia, suggesting that SPP1 mediated CD4+ T-cell and regulatory T-cell infiltration ( 29 ) ( Figure 1A ). Additionally, integrated analysis of bulk and single-cell RNA sequencing data showed that SPP1 was positively associated with myeloid cell infiltration but negatively associated with CD4/CD8 cell infiltration in the prognosis of patients with hepatocellular carcinoma ( 30 ) ( Figure 1A ).…”
Section: Spp1 Signaling and Immune Cellsmentioning
confidence: 99%
“…Tubulin α-1b chain (TUBA1B) is an important α-tubulin isoform with significant implications. For instance, it has been observed to impact immune cell infiltration within the tumor microenvironment of liver hepatocellular carcinoma (LIHC) and influence the responsiveness to immunotherapy, thereby significantly affecting their prognosis 8 , 9 , potentially attributed to TUBA1B overexpression, which has been linked to paclitaxel resistance in LIHC patients 10 . Additionally, TUBA1B has received attention for its upregulation in nephroblastoma 11 and its characterization as a crucial regulator in osteosarcoma 12 .…”
Section: Introductionmentioning
confidence: 99%